Art, sacred space and utopia - Cohen, Richard A. (Religija ir kultūra, 2008)
Monotheist religions oppose the idolatry which makes space sacred and the mythological world upon which all idolatry depends. Art, used by monotheisms and mythologies, is neutral in this opposition. The example of Judaism is invoked to show how two apparently “sacred spaces,” the ancient Temple in Jerusalem and the conjugal bed of the home, represent not sacralizations of places but displacements through the intensification of an ethical extra-territorial u-topos.
Keywords: Levinas; Art; sacred; Judaism; sexuality; utopia